The Impact of School Leadership Support on Teacher Retention: A Study among School Leaders and Teachers from a Private School in Sharjah - ISMAIL, SAMIH MOHAMMAD MOUSA (2024)
The dissertation delves into the pivotal challenge of teacher retention in private schools, spotlighting the influence of leadership practices on educators' decisions to remain. At its core, the investigation seeks to unravel how leadership within a private school setting in Sharjah impacts the stability of its teaching workforce. This inquiry is anchored by the main research question, which explores the role that leadership practices play in teacher retention in a private school in Sharjah. Drawing on a foundation of key theories and seminal studies in the realms of leadership styles, motivational frameworks, and teacher satisfaction, the dissertation crafts a comprehensive review of the existing literature. These theoretical underpinnings guide the investigation, offering insights into the dynamics between school leadership and teacher retention. Employing a mixed-methods approach, the study harnesses both quantitative data from surveys and qualitative insights from interviews with teachers. This methodology enables a nuanced understanding of the teachers' perceptions and experiences with leadership practices within their school environment. The investigation unveils that leadership qualities such as supportive gestures, recognition of efforts, and the provision of professional development opportunities play a significant role in teachers' decisions to stay. These findings underscore the importance of nurturing a positive work environment and the critical role school leaders play in fostering a sense of commitment among teachers. Acknowledging its limitations, including a constrained sample size and response rate, the study proposes avenues for future research. It suggests that further exploration into educational leadership and teacher satisfaction across more diverse and extensive educational